Patterns of poverty exposure and children's trajectories of externalizing and internalizing behaviors - Jinette Comeau; Michael H. Boyle (Elsevier, 2018)
Using data from the Child Supplement of the National Longitudinal Survey of Youth, we compare trajectories of externalizing and internalizing behaviors among children exposed to five patterns of poverty from birth to age 14: always or never poor - stable patterns; a single transition into or out of poverty, or repeated fluctuations in and out of poverty - changing patterns. We also examine how low maternal education and single parenthood interact with these poverty exposures to compound their adverse effects. Finally, we compare the magnitude of effects associated with the patterns of poverty exposure, as well as their interactions with low maternal education and single parenthood, on trajectories of externalizing and internalizing behaviors to determine if they are significantly different. Results reveal that initial levels and rates of change in children's trajectories of externalizing and internalizing behaviors are similar across the three changing patterns of poverty exposure, leading us to combine them into a single group representing intermittent poverty. Initial disparities between children who are never poor and their counterparts who are always or intermittently poor are constant over time for internalizing behaviors and grow in magnitude for externalizing behaviors. The cumulative negative effect of poverty exposure over time is stronger for externalizing vs. internalizing behaviors. Low maternal education compounds the adverse effects of persistent poverty, an effect that is similar for externalizing and internalizing behaviors. Keywords: United States, Poverty, Child mental health disparities, Externalizing behaviors, Internalizing behaviors, Multiple risk exposure